Case Report: Sudden Death of a Healthy Body Packer: A Case Study - Forouzesh, Mehdi; Fallah, Fardin (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: “Body packing” is concealing illegal substances in the digestive system for smuggling or transfer across borders and “body packers” are those who carry these substances. Illegal substances are wrapped in packages that are swallowed by body packers and delivered at destination by defecation. The most common fatal consequence of body packing is intoxication due to rupture of packages in the body. Due to secret nature of this form of smuggling, accurate statistics on its prevalence and complications are lacking. Iran is a big consumer of opioids, located in the route of transfer of illicit substances from Afghanistan to other parts of the world, and also implement tight restrictions on the carriage and distribution of opioids; thus rate of body packing is expected to be high in this country (especially for opioids). In this report we present a young man’s sudden death with unknown cause in central part of Iran that was referred for autopsy. Results: In the autopsy, 2237 g of opioid was found in his gastrointestinal system in the form of wrapped packages of which three were ruptured and caused fatal acute intoxication. The victim had no criminal records, however, he had psychological problems and was in low socioeconomic position. Conclusion: This report underlines the importance of primary prevention programs with focus on susceptible groups which are usually people from low socioeconomic groups and are unaware of health risks of body packing and take part in this trade for financial benefits.